(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The work concerns the iconographical, ideological and cultural relations between various sources dating from the time of Alfonso of Aragon, which are useful to define the king’s image and design his concept of majesty. Evidence for the king’s role models is given, in particular, by the field pavilion lavishly painted and given to the king in 1443 by the city of L’Aquila. Further evidence comes from the study of different tapestries commissioned by the monarch in Flanders as well as from a number of orations, laudatory works and panegyrics, written and dedicated to Alfonso by the humanists at his court. These models are represented by the stories and characters of the biblical and classical times, to which the king refers, once arrived in Italy, to legitimize himself under the guidance of the prominent intellectuals and artistes of the period. His purpose is to present his image as a sovereign depositary of all the Christian and humanist virtues and therefore as an obligatory point of reference for all the political forces, not only the Italian state powers of the era.